Mathematical modeling for learning algebraic operation - Diah Dwi Santri; Yusuf Hartono; Somakim Somakim (Intelektual Pustaka Media Utama, 2019)
This study aims to produce a learning trajectory using the mathematical modeling in helping students to understand the concept of algebraic operations. Therefore, the design research was chosen to meet the research aims and to give in formulating and developing local instructional theory in learning algebraic operations.Learning trajectory designed in the early phases and tested on 34 seven-grade students in SMP N 10 Palembang. Data collection was conducted through observation by recording the learning process that occured in the classroom and students’ group work was evidenced by video and photos. Data was analyzed qualitatively by describing actual learning which happened in pilot experiment and teaching experiment. There are 3 learning activities in the design of this study. These 3 activities are designed based on the steps of the Mathematical Modeling, activity 1 meaning of algebraic expressions, activity 2 addition of algebraic and activity 3 subtraction of algebraic. Based on the result, it can be concluded that activity which has been designed can help the students in learning algebraic operations using mathematical modeling. Used mathematical modeling can help student solve the problems and understand concept are structured using the assumptions and model start they design so gradually developed into formal mathematics.